Social Dialogue and Democracy in the Workplace Trade Union and Employer Perspectives from Turkey - Cam, Erdem; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on the experience of social dialogue in Turkey, which is a European Union candidate country. It argues that social dialogue constitutes one of the fundamental pillars of European social model and therefore should be analysed not only at the supranational level but also at the national, sectoral and workplace levels. The book critically examines social dialogue processes and mechanisms in Turkey at various levels, with focus on the workplace because it is shaped by socio-cultural elements which contain many variables. The book also identifies the shortcomings and structural impediments of social dialogue, and provides an empirically grounded theoretical explanation of social dialogue in Turkey. In the process, the book explains and clarifies key concepts to help readers grasp important points relevant to social dialogue, and contains interviews with social partners to take into consideration their views and recommendations on social dialogue. These in-depth interviews also provide a rare insight into the dynamics of social dialogue on the ground. By looking at social dialogue at various levels, the book offers a balanced view of its strengths and weaknesses in Turkey. This book is a valuable tool for students, academics and researchers interested in understanding the complex dynamics of social dialogue and workplace relations in Turkey. .
List of figures and tables -- Foreword -- Acknowledgement -- Abbreviations and acronyms -- Introduction -- Chapter 1 Concepts -- 1. Introduction -- 1.1. Social dialogue -- 1.1.1. Social partners in the context of class differences -- 1.1.2. Social dialogue in the workplace and democracy -- 1.1.3. Models providing social dialogue in the workplace -- 1.1.3.1. Representation on administrative and supervisory boards -- 1.1.3.2. Work councils -- 1.1.3.3. Expert boards -- 1.1.3.4. Workplace representation -- 1.1.4. Tripartite dialogue -- 1.1.5. Multilateral dialogue -- 1.2. Dialogue's power of influence in the decision making processes -- 1.3. Industrial democracy and social dialogue -- 1.4. Conclusion -- Chapter 2 Theoretical framework -- 2. Initial views on social dialogue -- 2.1. Confrontational approaches -- 2.1.1. Confrontational approach to industrial relations -- 2.1.2. Power relations in industrial relations -- 2.2. Conciliatory approaches -- 2.2.1. System theory -- 2.2.2. Pluralist approach -- 2.2.3. Human resources management approach -- Chapter 3 Method -- 3. Methodological background -- 3.1. Studying social dialogue from the social partners' perspective -- 3.2. Research question -- 3.3. Interviewed institutions -- 3.4. Process of contacting interviewees -- 3.5. Analysis of findings -- Chapter 4 The legal framework and scope of social dialogue at the workplace level in Turkey -- 4. Bilateral social dialogue in Turkish working life -- 4.1. Close pre-republic period -- 4.2. Post-republic period -- 4.2.1. Effects of classless social structure understanding -- 4.2.2. Collective bargaining and bilateral social dialogue -- 4.3. Other bilateral social dialogue applications -- 4.3.1. Representation and social dialogue in the workplace -- 4.3.1.1. Workers representation -- 4.3.1.2. Workplace union representation -- 4.3.2. Labour relations within the framework of boards -- 4.3.2.1. Boards structured by legislation -- A. Paid annual leave board -- B. Occupational health and safety board -- C. Commission for stopping and closing business -- D. Workplace health and safety units -- 4.3.2.2. Boards structured by collective bargaining -- A. Workplace disciplinary board -- B. Damage assessment board -- C. Industrial relations board -- D. Dispute resolution board -- 4.4. Conclusion -- Chapter 5 Opinions of social partners: Turkey, land of differences in labor relations -- 5. Different approach patterns among social partners -- 5.1. Union movement and social dialogue -- 5.1.1. Proletarianisation process in Turkey -- 5.1.2. Development of union movement and competition between unions -- 5.2. Barriers for freedom of association and collective bargaining -- 5.2.1. Low bargaining means low social dialogue -- 5.2.2. Effects caused by sectoral and workplace thresholds for collective bargaining -- 5.2.3. Disunionisation efforts and decentralised relations -- 5.3. Subcontracting and social dialogue -- 5.4. Competition -productivity and social dialogue -- 5.5. Workplace level social dialogue in the European Union process -- 5.5.1. Pressures on Turkey -- 5.5.2. Differences in approach between European and Turkish employers -- 5.6. Workplace boards and social dialogue -- 5.7. Worker representation and volunteer boards -- 5.7.1. Can worker representation be an option? -- 5.8. Social partnership and social dialogue -- 5.9. Socio-cultural values and social dialogue -- 5.10. An attempt to explain Turkish labor relations theoretically -- Discussion and conclusion -- Bibliography -- Annexes -- List of figures and tables.
Keywords: Psychology, Industrial; Economic sociology; Social legislation; Work and Organizational Psychology; Economic Sociology; Labour Law/Social Law